Distinct ionic adsorption sites in defective Prussian blue: a 3D-RISM study. Issue 40 (7th October 2019) - Ruankaew, Nirun; Yoshida, Norio; Watanabe, Yoshihiro; Nakayama, Akira; Nakano, Haruyuki; Phongphanphanee, Saree
Abstract : The adsorption site of alkali ions in defective Prussian blue. Abstract : Ferric hexacyanoferrate (FeHCF) or Prussian blue (PB) exhibits selective alkali ion adsorption and has great potential for use in various applications. In the present work, alkali ion (Li +, Na +, K +, and Cs + ) and water configurations in defective PB (d-PB) were studied by using the statistical mechanics of molecular liquids. The three-dimensional (3D) distribution functions of the ions and water were determined by solving the 3D-reference interaction site model (RISM) equation of systems of a unit lattice of d-PB in electrolyte solutions, i.e., LiCl, NaCl, KCl, and CsCl. The results show the difference in the ion–water configurations and distributions between small (Li + and Na + ) and large ions (K + and Cs + ). The adsorption sites of Li + and Na + are located off-center and lie on the diagonal axis. By contrast, the larger ions, K + and Cs +, are adsorbed at the center of the unit cell. The degree of dehydration due to the adsorption of alkali ions indicates that there was no water exchange during Li + and Na + adsorption, whereas two and three water molecules were removed after adsorption of K + or Cs + in the unit cell.